2022
DOI: 10.1111/boer.12364
|View full text |Cite
|
Sign up to set email alerts
|

FDI inflows, economic growth, and governance quality trilogy in developing countries: A panel VAR analysis

Abstract: This study provides evidence of the triangular relationship between governance quality, foreign direct investment, and economic growth. Unlike previous studies in the governance-foreign direct investment-growth literature, this study employed the panel vector autoregressive model to examine the impact of governance quality and foreign direct investment on economic growth. Moreover, we used the impulse response function tool, which was developed in the same context, to better understand the reaction of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 95 publications
1
13
0
1
Order By: Relevance
“…Sabir et al (2019) also observed a positive association between FDI inflows and trade openness in developing countries, as did Kurul and Yalta (2017). Saidi et al (2013) also observed that trade openness is positively related to FDI inflows in 20 developed and developing economies during 1998-2011. However, trade openness is not an FDI determinant for the CIVETS.…”
Section: Discussionmentioning
confidence: 67%
“…Sabir et al (2019) also observed a positive association between FDI inflows and trade openness in developing countries, as did Kurul and Yalta (2017). Saidi et al (2013) also observed that trade openness is positively related to FDI inflows in 20 developed and developing economies during 1998-2011. However, trade openness is not an FDI determinant for the CIVETS.…”
Section: Discussionmentioning
confidence: 67%
“…The choice of our variables was informed by previous studies such as Hermes and Lensink (2003), Alfaro et al (2004), Blonigen and Wang (2005), Mengistus and Adams (2007), Alleyne and Edwards (2011), Nguyen and To (2017), Raheem and Oyinlola (2013), Saidi et al (2022), and Ochi et al (2022). Economic growth is measured by annual rate of GDP per capita growth.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…They find that the governance quality plays an important role in improving the impact of government expenditure. By applying the panel vector autoregressive (PVAR) model, Saidi et al (2022) examine the triangular relationship between governance quality, FDI, and economic growth for 102 developing countries from 1996 to 2014. They find that inward FDI has a significant impact and can strongly encourage economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Globalization promotes more significant levels of innovation and technology, encouraging entrepreneurship in competitive markets and increasing access to markets, resulting in longer-term growth at constant returns (Krueger & Berg, 2003;Ngepah & Udeagha, 2019;Ngepah, 2014). Foreign direct investment (FDI) has increased due to globalization, and open economics has become more appealing to FDI as their governments have adopted liberal investment policies (Saidi et al, 2013). Foreign direct investment is critical for economic growth and poverty alleviation.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign direct investment is critical for economic growth and poverty alleviation. Foreign investments help in employment generation, technological transfer, and, as a result, the host country's development and economic progress (Berden et al, 2014;Saidi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%